Jugoslawische Gewerkschaften. Monatsbulletin des Zentralausschusses des Gewerkschaftsbundes Jugoslawiens
Engl. ed.: Yugoslav trade unions. Publ. by the Central council...(ZK 56515). - French ed.: Syndicats yougoslaves. Ed. par le Conseil central...